Administrative management and organizational commitment in the provincial Municipality of Ilo, 2023 - Vizcarra Canaza, Roy Eduardo (2024)
The purpose is to analyze the association of administrative management and organizational commitment in the Provincial Municipality of Ilo, 2023. Method. The design is observational and cross-sectional; the population sample is 310 employees established through simple probabilistic sampling. To obtain the data, a survey was used, duly prepared in two questionnaires with 24 questions for each variable. Results. 51.10% of workers value the development of administrative management as effective, which is reflected in the optimization of resources, communication with community representatives, 58.80% show a high level of organizational commitment to achieving objectives, teamwork, proactive initiative to improve processes and services, great sense of responsibility and belonging. It is concluded that administrative management is directly significantly and very highly associated (81.60%) with the organizational commitment of workers, likewise, its dimensions have a significant association.